2015
DOI: 10.1186/s13046-015-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of potential prognostic lncRNA biomarkers for predicting survival in patients with multiple myeloma

Abstract: BackgroundDysregulated long non-coding RNAs (lncRNAs) have been found to have oncogenic and/or tumor suppressive roles in the development and progression of cancer, implying their potentials as novel independent biomarkers for cancer diagnosis and prognosis. However, the prognostic significance of expression profile-based lncRNA signature for outcome prediction in patients with multiple myeloma (MM) has not yet been investigated.MethodsLncRNA expression profiles of a large cohort of patients with MM were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 47 publications
0
153
0
Order By: Relevance
“…Different groups of cells were seeded into 6 wells plate at 1x10 5 cells per well. The cell number was counted for three consecutive days and then growth curve was drawn according to the cell number at 24, 48 and 72 h. 1x10 6 cells were prepared for cell cycle analysis. First, the cells were fixed with 70% cold ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different groups of cells were seeded into 6 wells plate at 1x10 5 cells per well. The cell number was counted for three consecutive days and then growth curve was drawn according to the cell number at 24, 48 and 72 h. 1x10 6 cells were prepared for cell cycle analysis. First, the cells were fixed with 70% cold ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, lncRNAs also have the potential function as diagnostic or prognostic markers of cancer (4)(5)(6)(7)(8)(9)(10). Nuclear enriched abundant transcript 1 (NEAT1) is a nuclear-restricted lncRNA that has two isoforms: NEAT1-1 and NEAT1-2 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profilings of highly purified bone marrow plasma cells performed in newly diagnosed patients with MM, GSE24080, 22 were downloaded from Gene Expression Omnibus (GEO) database (http://www.ncbi. nlm.nih.gov/geo/).…”
Section: Data Source and Patient Informationmentioning
confidence: 99%
“…It has been revealed that lncRNAs are involved in the development and progression of tumors, and that their abnormal expression is associated with tumor proliferation, apoptosis, the cell cycle, angiogenesis, recurrence and metastasis in numerous different types of cancer (4,5). Previous studies have demonstrated the potential roles of lncRNAs to serve as diagnostic markers and therapeutic targets for cancers (6)(7)(8)(9)(10)(11)(12)(13)(14). However, the role and mechanism of lncRNAs in ECC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%